Requirement Model For Mobile Bus Rental And Reservation Application - Abuzwida, Bashir R. B. (2008)
The main objectives of this study are to design a bus rental and reservation system for searching the availability of bus, the price of bus rental, and reserve the bus, to develop a system of the Bus Rental and Reservation System. The design is tested on the prototype and evaluated to test the usability and acceptability of the system. The Wireless Application Protocol (WAP) technologies have been used in this application has enable users to make booking through mobile telephones.